2012
DOI: 10.1186/1472-6947-12-102
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of health service infrastructure and policy impacts on access to computerised CBT in Scotland

Abstract: BackgroundNICE recommends computerised cognitive behavioural therapy (cCBT) for the treatment of several mental health problems such as anxiety and depression. cCBT may be one way that services can reduce waiting lists and improve capacity and efficiency. However, there is some doubt about the extent to which the National Health Service (NHS) in the UK is embracing this new health technology in practice. This study aimed to investigate Scottish health service infrastructure and policies that promote or impede … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The implementation of cCBT will also aid the achievement of the NHS targets as it allows the treatment of high numbers of patients with minimal therapeutic input. However, the results of a recent survey of Scottish NHS boards indicated that NHS policy and infrastructure may not be fully in place to support to implementation of cCBT in many areas [17]. Overall, most of the health boards possess the required software to use cCBT programs.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of cCBT will also aid the achievement of the NHS targets as it allows the treatment of high numbers of patients with minimal therapeutic input. However, the results of a recent survey of Scottish NHS boards indicated that NHS policy and infrastructure may not be fully in place to support to implementation of cCBT in many areas [17]. Overall, most of the health boards possess the required software to use cCBT programs.…”
Section: Discussionmentioning
confidence: 99%
“…This is not unexpected for this sample of people recruited online. However, our recent national surveys of access to online resources via the NHS in Scotland (Kenicer, McClay and Williams, 2012) and England (Andrewes, Kenicer, McClay and Williams, 2013) has identified a lack of provision for those who do not have their own access to computers at home. In effect this means that those who are unemployed or older may have limited opportunity to access such resources.…”
Section: Anticipated Problems In Using Online Self-helpmentioning
confidence: 99%
“…However, IT policies were more likely to be restrictive in Scotland with English trusts being more than twice as likely to provide patients with computer and internet access, and significantly more likely to allow patients access to cCBT sites on their computers. 18 No other studies to date have audited the accessibility of cCBT within NHS trusts. A limitation of this study includes the knowledge of the IT representatives completing the survey.…”
Section: Discussionmentioning
confidence: 99%
“…17 Despite this, a recent national survey of the provision of cCBT within Scottish National Health Service (NHS) mental health boards highlighted that patient accessibility to cCBT within the NHS is restricted by local Information Technology (IT) policies, software and equipment availability. 18 That survey found that 64% of health boards do not provide dedicated computers for patient use, and 36% do not permit members of staff to offer email contact or support to patients. This means that email support sessions (a valuable component of the guided self-help approach) cannot be delivered.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation